Hispania, A journal devoted to the interests of the teaching of Spanish and Portuguese, published by the American Association of Teachers of Spanish and Portuguese, Cincinnati (Ohio), University of Cincinnati, vol. 68, núms. 1, 2, 3 y 4 de 1985. - Valencia Zuluaga, José Néstor (Thesavrvs, 2023)
Reseñas de revistas.